EVALUATION OF PROPOFOL AND ETOMIDATE AS ANESTHETIC AGENTS IN ELECTROCONVULSIVE THERAPY -A RETROSPECTIVE OBSERVATIONAL STUDY - Dr. Fidah Mohamed; Dr. Mahparah Rafiq; Dr. Mudhabir Ashraf (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Electroconvulsive therapy (ECT) remains a cornerstone in the treatment of severe psychiatric illnesses such as treatment-resistant depression, catatonia, and certain forms of schizophrenia. Anesthetic agents used during ECT significantly influence the quality of the induced seizure, hemodynamic response, recovery characteristics, and overall patient safety. Among the agents commonly used, etomidate is known for its seizure-prolonging properties, whereas propofol offers smoother induction and hemodynamic stability. Aim: To retrospectively compare the effects of etomidate and propofol on seizure duration, hemodynamic parameters, and recovery characteristics during ECT in adult patients. Methods: A retrospective observational study was conducted at Institute of Mental health and neurosciences Kashmir an associated hospital of Government Medical College Srinagar in the department of Psychiatry and Anesthesiology, including 120 adult patients who received a total of 480 ECT sessions (240 with etomidate and 240 with propofol) between January 2023 and July 2025. Data were collected from anesthesia and ECT records, including demographic details, anesthetic dose, seizure duration, pre- and post-procedure vitals, and recovery times. Results: The mean motor seizure duration was significantly longer in the etomidate group (52.6 ± 9.2 seconds) compared to the propofol group (28.4 ± 7.1 seconds; p < 0.001). Mean systolic blood pressure post-ECT increased by 18.4 mmHg in the etomidate group versus 9.2 mmHg in the propofol group (p = 0.02). Myoclonus was observed in 14.2% of patients given etomidate but in none of the propofol group. Recovery time, defined as return to baseline orientation, was comparable between groups: 9.8 ± 2.1 minutes for etomidate vs. 9.2 ± 2.3 minutes for propofol (p = 0.28). No serious adverse events were reported in either group. Conclusion: Etomidate is associated with significantly longer seizure durations, making it potentially more effective in enhancing the therapeutic efficacy of ECT. However, its use is accompanied by a higher incidence of transient hypertension and myoclonus. Propofol offers superior hemodynamic stability but may compromise seizure quality due to its anticonvulsant properties. The choice of anesthetic should be tailored to patient-specific cardiovascular status and therapeutic goals.